The Influence of Service Quality and Brand Image on Increasing Mobile Phone Sales at Mitracell Store, Sibolga - Tiorida Pandiangan; Safriadi Pohan; Yusi Tri Utari Panggabean (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the effect of Service Quality and Brand Image on mobile phone sales at Mitracell Store in Sibolga. The research employed a quantitative approach with a descriptive associative design. The population consisted of 300 consumers, with 45 respondents selected as the research sample. Data analysis was conducted through classical assumption tests (normality, heteroscedasticity, and multicollinearity tests), as well as correlation coefficient analysis, coefficient of determination (R²), multiple linear regression analysis, partial tests (t-test), and simultaneous testing (F-test/ANOVA). The findings indicate that Service Quality has a moderate positive correlation with Sales (r = 0.448), while Brand Image shows a low positive correlation with Sales (r = 0.357). The multiple regression equation obtained is Y = 18.325 + 0.483X₁ + 0.016X₂. Partially, Service Quality (t = 1.963 < 2.016; p = 0.056 > 0.05) and Brand Image (t = 0.073 < 2.016; p = 0.942 > 0.05) do not have a statistically significant effect on Sales. The coefficient of determination (R²) of 0.201 indicates that 20.1% of the variation in Sales can be explained by Service Quality and Brand Image, while the remaining 79.9% is influenced by other factors outside the research model. However, simultaneously, Service Quality and Brand Image have a significant effect on Sales (F = 5.277 > 3.21; p = 0.009 < 0.05).